Effect of Monomer Application for Different Time Periods on Bond Strength between Heat Cured Denture Base Resin and Acrylic Resin Teeth - Beenish Mehtab, Kashif Aslam, Muhammad Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out the effect of monomer application for different time periods on tensile bond strength of heat cured denture base resin and acrylic resin teeth. Methodology: Ninety specimens were fabricated as per ADA standards No 15 and were divided into 3 groups through purposive sampling technique. In Group 1 monomer was applied on acrylic resin teeth just before heat cured denture base material was packed. In Group 2 monomer was applied for 10 seconds and in Group 3 for 60 seconds. Universal testing machine applied tensile load between denture base and acrylic teeth. Visual observation was done to detect types of failure. Result: Group 2 showed the highest value of tensile bond strength followed by Group 1 and 2 however there was no statistically significant (p>0.05) difference between the groups. Practical implication: Monomer application enhances bond strength between denture base and acrylic teeth but time period of its application which could provide maximum benefit is not very clear. Therefore this study is carried out so that the most effective time period of its application can be figured out. Conclusion: Bond strength was not affected by monomer application for different time periods. Keywords: Monomer, Time period, Denture base resin, Acrylic teeth